2017
DOI: 10.1093/hmg/ddx064
|View full text |Cite
|
Sign up to set email alerts
|

Golgi-retained Cx32 mutants interfere with gene addition therapy for CMT1X

Abstract: Numerous GJB1 gene mutations cause the X-linked form of Charcot-Marie-Tooth disease (CMT1X). GJB1 encodes connexin32 (Cx32), which forms trans-myelin gap junctions in Schwann cells. Most GJB1 mutations result in loss-of-function mechanisms, supporting the concept of gene replacement therapy. However, interactions between delivered wild type and endogenously expressed mutant Cx32 may potentially occur in the setting of gene replacement therapy. In order to screen for possible interactions of several representat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…In those particular mutations, the virally delivered gene therapy does not traffic normally to deliver therapy optimally. Thus, screening for mutant-wild type interaction will be an important caveat to gene replacement therapy strategies [84]. In the proper context, gene replacement therapy might lead to a viable treatment option.…”
Section: Cmtx1mentioning
confidence: 99%
“…In those particular mutations, the virally delivered gene therapy does not traffic normally to deliver therapy optimally. Thus, screening for mutant-wild type interaction will be an important caveat to gene replacement therapy strategies [84]. In the proper context, gene replacement therapy might lead to a viable treatment option.…”
Section: Cmtx1mentioning
confidence: 99%
“…Cx26 variants associated with hearing loss showed intracellular retention in the ER or in the early endosomes, and their loss of function appears to be due to premature degradation (Xiao et al, 2011;Beach et al, 2020). Several Cx32 mutants causing neuropathy showed complete absence (Sargiannidou et al, 2015) or abnormal intracellular retention in the ER and/or Golgi (Kleopa et al, 2002(Kleopa et al, , 2006, often with dominant effects on co-expressed WT Cx32 with demonstrated direct protein-protein interaction, likely during hexamer formation in the Golgi (Kyriakoudi et al, 2017). Other Cx32 mutants reached the cell membrane but showed shifted voltage gating and abnormally increased opening of the channels (Abrams et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Virally delivered wild-type (WT) Cx32 could be detected in the non-compact myelin of T55I KO mice, but only rarely in N175D KO or R75W KO mice, suggesting dominant-negative effects of the R75W and N175D mutants but not of the T55I mutant on co-expressed WT Cx32 [77]. Further, in vitro Cx32 WT-mutant co-expression studies demonstrated directly that certain Golgi-retained CMT1X mutants may interfere with expression and intracellular trafficking of WT Cx32 [78], and could thus potentially interfere with gene addition therapy for CMT1X.…”
Section: Genetic Models Of Oligodendrocyte Connexins and Gene Replacementioning
confidence: 98%